An Analysis of Code Switching as a Communication Strategy among the Students in Pandemic Era - Asteria eka prasasty (Journal Corner of Education, Linguistics, and Literature, 2022)
This research is aimed at finding out the types of code switching used by English Language Students at Lampung University as their communication strategy. Moreover, the writer uses descriptive qualitative method by collecting the selected data for the research. In determining the types of code switching, the writer paid attention to the student’s conversation during the presentation. In collecting the data for the research, the writer followed some steps. Firstly, the writer observed the student’s activity in the class room and recording the activity and also the conversation. Secondly, the writer watched again the recorded data which contains of codes language that used by the students. Thirdly, the writer chooses the utterances that consisted of code switching. Forthly, the writer wrote down the data into table. The final step is to analyze the data based on the types and the factors of code switching.Finding reveal that there are two types of code switching used by the students, inter and intra sentential code switching.